Penentuan E-Wallet Terbaik dengan Metode Simple Additive Weighting (SAW) dan Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) - Mohamad Tafrikan; Ariska Kurnia Rachmawati; Atika Dewi Ardiyanti; Rindi Saputri; Sholifatun Umayah (Universitas Wahid Hasyim, 2023)
Currently, many purchases of goods can be found electronically or known as e-wallets. E-wallet is a form of Fintech (Finance Technology) that utilizes internet media and is used as an alternative payment method. Several other types of e-wallets: Dana, Shopeepay, Gopay, Ovo, Sakuku. This study discusses the best recommendations among types of E-wallet using the Simple Additive Weighting (SAW) method and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). Both of these methods are able to make more accurate assessments and predetermined preference weights. Based on calculations using the SAW and TOPSIS methods, the first best e-wallet ranking is DANA, the second is Shopeepay, and the third is Gopay.